THE EFFECT OF DIRECT CASH ASSISTANCE IMPLEMENTATION AND VILLAGE FUND POLICY ON COMMUNITY WELFARE IN GAMPONG LAMBHUK, ULEE KARENG - Ricky Ariansyah; Husnul Muna (RADJA PUBLIKA, 2026)
This study analyzes the effect of Direct Cash Assistance (BLT) implementation and Village Fund policy on community welfare in Gampong Lambhuk, Ulee Kareng District. It employed an explanatory quantitative approach with a cross-sectional survey design. The population consisted of 149 BLT recipients, and a sample of 109 respondents was determined using the Slovin formula. Data were collected through a Likert-scale questionnaire and analyzed using descriptive statistics, data-quality tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results show that BLT implementation has a positive and significant effect on community welfare (B = 0.522; t = 5.615; p < 0.001). Village Fund policy has no significant partial effect (B = 0.019; t = 0.189; p = 0.850). Simultaneously, both variables have a significant effect (F = 26.884; p < 0.001) and explain 33.7% of the variance in welfare. The findings emphasize the importance of accurately targeting BLT recipients and strengthening governance, transparency, and community participation in the use of Village Funds.